A MAX phase ceramic reinforced high temperature resistant composite friction material and preparation method thereof
By adding composite reinforced phases and composite lubricated phases to the copper alloy matrix, and through high-energy ball milling and high-temperature sintering processes, the problem of insufficient tribological properties of copper alloy materials in high-temperature environments is solved, and excellent mechanical properties and wear resistance are achieved.
Patent Information
- Application Number
- CN202410707491.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-03
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2044-06-03
AI Technical Summary
Traditional copper alloy materials have insufficient tribological properties in high-temperature oil-free environments, resulting in a rapid decline in friction coefficient and service life, affecting the safety and reliability of components.
Add composite reinforced phase (Ti3SiC2+TiC+TiB2) and composite lubricated phase (K2MoO4+MoS2) to the copper alloy matrix. Through high-energy ball milling and high-temperature sintering processes, uniform dispersion and effective coupling between the reinforced phase and the lubricated phase are achieved.
It realizes excellent mechanical properties and wear resistance of copper alloy materials in high temperature environments, reduces friction coefficient and wear rate, and extends service life.
Smart Images

Figure CN118773472B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a MAX phase ceramic reinforced high temperature resistant composite friction material and a preparation method thereof, belonging to the technical field of copper alloys. Background Art
[0002] Copper-based composite materials have excellent mechanical properties, tribological properties, corrosion resistance, and electrical and thermal conductivity, and are widely used in mechanical processing, transportation, electricity, energy and other fields, such as sliding bearings, pantograph slides, clutch friction plates, etc. Experiments have shown that the adhesive wear mechanism of copper alloy parts intensifies during long-term friction and wear, and the wear rate increases rapidly, resulting in a rapid decrease in the friction coefficient and service life, which in turn affects the safety and reliability of the parts. Therefore, how to improve the tribological properties of copper alloy materials in high-temperature oil-free environments is a problem worthy of attention.
[0003] Patents CN112011748B and CN110284083B improve the heat resistance and service life of materials by adding carbon fiber to copper alloys, but as the carbon fiber content increases, the initiation and expansion of cracks inside the material intensify, which will have an adverse effect on the mechanical properties. Patent application CN10820666A effectively reduces the friction coefficient and wear rate by adding BN to the copper matrix, but the matrix of this material is pure copper, and the strength and wear resistance are insufficient when used for parts with large shear stress. Patent application CN109518100A prepares copper alloy powder metallurgy materials with excellent tribological properties. Although the addition of graphite effectively reduces the friction coefficient, due to its poor surface wettability with the copper matrix, when the total graphite content exceeds 20%, the wear resistance and mechanical strength of the material are greatly reduced. Patent CN102703161A improves the self-lubricating properties of the material by adding an appropriate amount of MAX phase ceramic Ti3SiC2 to pure copper. However, its base is pure copper, and its strength and hardness are much lower than copper alloy, which limits its use in heavy load and strong impact conditions. n+1 XA n Compounds are added to the brake pad material for strengthening. Its matrix is copper-iron-nickel alloy, which does not contain aluminum and has poor corrosion resistance. n+1 XA nThe addition amount of the compound is 15-35%. A higher content reduces the toughness and strength of the matrix. In addition, the patent does not add a lubricating phase, and the friction coefficient is relatively high. The above research results show that the strengthening effect of the traditional strengthening phase on the copper alloy matrix is limited, and when the content is high, it will have an adverse effect on the uniformity of the material's organization and mechanical strength; at the same time, the modification effect of a single strengthening phase or lubricating phase is limited, and the strengthening phase and the lubricating phase need to be matched to produce a coupling effect in order to reduce wear while maintaining a stable friction coefficient. Therefore, it is necessary to study new composite strengthening phase and composite lubricating phase formulas and material preparation methods to further improve the friction and wear performance of copper alloys at high temperatures.
[0004] Studies have shown that adding alloying elements to copper alloys can improve hardness and strength, but there is no report on compounding Co and La2O3 to improve the wear resistance of copper alloys. At the same time, Ti3SiC2, TiC, and TiB2 all have high hardness, and the high-temperature oxidation products of Ti3SiC2 can play an effective anti-wear and friction-reducing role, making the material show better wear resistance. Researchers have studied the friction properties of Ti3SiC2, TiC, and TiB2, but there is no report on preparing a composite strengthening phase (Ti3SiC2+TiC+TiB2) and adding it to copper-iron alloys to enhance wear resistance. In addition, K2MoO4 will form a lubricating film on the friction surface at high temperatures, keeping the friction coefficient low and stable; MoS2 can reduce the damage of hard wear debris to the friction surface, thereby weakening the abrasive wear mechanism. The existing technology has realized the use of K2MoO4 and MoS2, but there is little research on regulating their ratio and addition amount to improve the lubrication performance of copper alloys. There is also no research on adding composite strengthening phases (Ti3SiC2+TiC+TiB2) and composite lubricating phases (K2MoO4+MoS2) into copper alloys and precisely regulating their mutual coupling properties.
[0005] Based on the above research status, the present invention provides a method for strengthening a copper alloy matrix by precisely controlling the addition amounts of Co and La2O3; provides a method for preparing and adding a composite strengthening phase (Ti3SiC2+TiC+TiB2) so that the copper alloy has both good mechanical properties and anti-wear properties; provides a method for preparing a composite lubricating phase (K2MoO4+MoS2) and regulating its ratio so that the high-temperature lubrication performance of K2MoO4 is combined with the room-temperature lubrication performance of MoS2; provides a method for simultaneously adding a composite strengthening phase (Ti3SiC2+TiC+TiB2) and a composite lubricating phase (K2MoO4+MoS2) so that the adhesive wear weakening effect of (Ti3SiC2+TiC+TiB2) and the abrasive wear weakening effect of (K2MoO4+MoS2) are coupled to each other; provides a MAX phase ceramic reinforced high-temperature resistant composite friction material and a preparation method. Summary of the invention
[0006] In view of this, the object of the present invention is to provide a MAX phase ceramic reinforced high temperature resistant composite friction material and a preparation method. By adding a reinforcing phase (Ti3SiC2+TiC+TiB2) and a composite lubricating phase (K2MoO4+MoS2) to a copper alloy matrix, a composite material with excellent mechanical properties and tribological properties can be obtained through coupling. After high-energy ball milling and high-temperature sintering of the composite reinforcing phase (Ti3SiC2+TiC+TiB2), TiC and TiB2 can have a reinforcing effect on Ti3SiC2, thereby improving the reinforcing effect on the matrix, and the increase in surface chemical energy makes the interface with the matrix more firmly bonded. The composite reinforcing phase can reduce the furrowing and peeling effects of the contact surface through the pinning mechanism, better disperse the shear stress during the friction process, thereby reducing the wear rate and making the material show better wear resistance. At the same time, the composite lubricating phase (K2MoO4+MoS2) will form a lubricating film on the friction surface at high temperature, so that the friction coefficient remains low and stable, and reduces the damage of hard wear debris to the friction surface. Through the mutual coupling of the composite reinforcement phase and the composite lubrication phase, the mechanical properties and friction of the material are taken into consideration.
[0007] To achieve the above objectives, the technical solution of the present invention is as follows.
[0008] A MAX phase ceramic reinforced high temperature resistant composite friction material, with the total mass of the material being 100%, the components and their mass percentages are: 76.0% to 94.0% copper alloy matrix, 3.0% to 12.0% composite reinforcement phase, and 3.0% to 12.0% composite lubrication phase; wherein the composite reinforcement phase is composed of Ti3SiC2, TiC and TiB2, the mass fraction of Ti3SiC2 in the composite reinforcement phase is 60.0% to 80.0%, the mass fraction of TiC is 10.0% to 20.0%, and the mass fraction of TiB2 is 10.0% to 20.0%; the composite lubrication phase is composed of K2MoO4 and MoS2, the mass fraction of K2MoO4 is 40.0% to 60.0%, and the mass fraction of MoS2 is 40.0% to 60.0%; the material is obtained by ball milling and hot pressing sintering of the copper alloy matrix, the composite reinforcement phase and the composite lubrication phase.
[0009] Preferably, taking the total mass of the material as 100%, the components and their mass percentages are: Cu 58.0% to 77.0%, Al 6.0% to 9.5%, Ni 4.0% to 6.5%, Fe 2.5% to 4.0%, Mn 0.3% to 1.0%, Co 0.3% to 1.0%, La2O3 0.3% to 1.0%, composite strengthening phase 3.0% to 12.0%, and composite lubrication phase 3.0% to 12.0%.
[0010] Preferably, the mesh size of the composite reinforcement phase is 200-300 meshes.
[0011] Preferably, the mesh size of the composite lubricating phase is 200-300 meshes.
[0012] A method for preparing the MAX phase ceramic-reinforced high-temperature-resistant copper-based composite friction material of the present invention comprises the following steps:
[0013] (1) Ti3SiC2, TiC and TiB2 powders are mixed and wet-milled under inert gas protection, with a ball-to-material ratio of 4:1 to 6:1, a rotation speed of 250 to 350 r / min, and a ball milling time of 8 to 12 h to obtain a mixed powder; the mixed powder is placed in a sintering furnace for sintering, and the vacuum degree is less than or equal to 1×10 -1 Pa, sintering temperature is 1200-1400℃, holding time is 5-10min, after sintering, the furnace is cooled, and the obtained block is ground under inert gas protection to obtain composite strengthening phase powder;
[0014] (2) mixing the copper alloy matrix, the composite strengthening phase powder and the composite lubricating phase powder, and ball milling them under inert gas protection, with a ball-to-material ratio of 1:1 to 2:1, a rotation speed of 100 to 150 r / min, and a ball milling time of 10 to 12 h to obtain a mixed powder;
[0015] (3) The mixed powder is placed in a sintering furnace for sintering, and the vacuum degree is less than or equal to 1×10 -1 Pa, the sintering temperature is 850-900℃, the sintering pressure is 35-40MPa, the holding time is 5-10min, and the furnace is cooled after sintering to obtain a MAX phase ceramic reinforced high temperature resistant composite friction material.
[0016] Preferably, in step (1), the heating rate is 100-150° C. / min.
[0017] Preferably, in step (1), during grinding, the grinding jar and the grinding balls are both made of tungsten carbide, the ball-to-material ratio is 1:1-2:1, the rotation speed is 100-150 r / min, and the grinding time is 6-8 h.
[0018] Preferably, in step (1), during grinding, the grinding is stopped every 10 minutes, and then continued after stopping for 2 minutes.
[0019] Preferably, in step (2), during ball milling, both the grinding jar and the grinding balls are made of tungsten carbide cemented carbide.
[0020] Preferably, in step (2), during ball milling, the mill is stopped every 5 minutes and then continued to run after stopping for 2 minutes.
[0021] Preferably, in step (3), during sintering, the heating rate is 100 to 150° C. / min.
[0022] Beneficial Effects
[0023] 1. The present invention provides a MAX phase ceramic reinforced high temperature resistant composite friction material, which adds a composite strengthening phase (Ti3SiC2+TiC+TiB2) to a copper alloy matrix, reduces the furrowing and peeling effects of the contact surface through a pinning mechanism without affecting the strength of the matrix, and improves the wear resistance and service life of the matrix under high temperature dry friction conditions. The ratio of each substance in the composite strengthening phase will have a significant impact on the mechanical properties and friction properties of the material. If Ti3SiC2 is too little and TiC and TiB2 are too much, the interface bonding force between the composite strengthening phase and the copper alloy matrix decreases, resulting in a decrease in the bending strength and compressive strength of the material; if Ti3SiC2 is too much and TiC and TiB2 are too little, TiC and TiB cannot play a strengthening role on Ti3SiC2 and the copper alloy matrix, resulting in an insignificant improvement in the wear resistance of the material. Compared with copper-iron alloys with commonly used strengthening phases such as Al2O3, the present invention achieves a balance between mechanical properties and wear resistance by accurately controlling the content of Ti3SiC2, TiC, and TiB2.
[0024] 2. The present invention provides a MAX phase ceramic-reinforced high-temperature resistant composite friction material. The material can form a hard, stable separation film with low shear force on the friction surface by adding a composite lubricating phase (K2MoO4+MoS2) to a copper alloy matrix, thereby improving the friction reduction performance of the matrix under extreme braking high-temperature conditions. The content of K2MoO4 and MoS2 will have a significant impact on the material properties. If there is too much K2MoO4 and too little MoS2, the lubrication performance of the material at room temperature will decrease; if there is too little K2MoO4 and too much MoS2, it is difficult to effectively improve the lubrication performance of the material under high-temperature conditions. Compared with copper-iron alloys that add commonly used lubricating phases such as graphite, the present invention has a low and stable friction coefficient at room temperature and high-temperature conditions by accurately controlling the content of K2MoO4 and MoS2.
[0025] 3. The present invention provides a MAX phase ceramic reinforced high temperature resistant composite friction material, which improves wear resistance by adding a specific content of composite strengthening phase (Ti3SiC2+TiC+TiB2) in a copper alloy matrix, and reduces friction coefficient by adding a specific content of composite lubricating phase (K2MoO4+MoS2). Compared with materials containing only one added phase, the present invention achieves the coupling of lubrication and anti-friction performance under room temperature and high temperature conditions through the synergistic effect between the components, so that the composite friction material has excellent mechanical properties, wear resistance and lubrication properties.
[0026] 4. The present invention provides a MAX phase ceramic reinforced high temperature resistant composite friction material, wherein the material produces solid solution strengthening by adding Co element to the copper alloy matrix and produces dispersion strengthening by adding La2O3 dispersedly distributed in the matrix. Compared with the existing matrix strengthening technology, the present invention combines the solid solution strengthening effect of Co element with the dispersion strengthening effect of La2O3 by accurately controlling the relative content of Co and La2O3, so that the material has excellent structural uniformity, hardness and strength.
[0027] 5. The present invention provides a method for preparing a MAX phase ceramic-reinforced high-temperature resistant composite friction material, wherein the composite reinforcement phase (Ti3SiC2+TiC+TiB2) is prepared by high-energy ball milling and high-temperature sintering of Ti3SiC2 powder, TiC powder, and TiB2 powder. By high-energy ball milling of the Ti3SiC2+TiC+TiB2 mixed powder, the uniformity and surface chemical energy of the composite reinforcement phase are improved, making it easier to be evenly distributed in the matrix during hot pressing sintering, and improving the bonding force with the matrix interface; then, by high-temperature sintering, a reinforcement effect is generated between the composite reinforcement phases, thereby further improving the hardness of the reinforcement phase, and improving the reinforcement effect of the reinforcement phase on the matrix.
[0028] 6. The present invention provides a method for preparing a composite modified high temperature resistant friction material, in which copper alloy powder, (Ti3SiC2+TiC+TiB2) powder and (K2MoO4+MoS2) powder are ball milled under the protection of an inert gas, and the obtained mixed powder is placed in a sintering furnace for hot pressing and sintering, and then cooled in the furnace after sintering. Compared with the existing preparation technology, the preparation process of the present invention is obtained through multiple experiments, which can improve the uniformity and strength of the material's structure on the one hand, and the density and hardness on the other hand. In addition, the preparation process is simple, and the targeted regulation of material properties can be achieved by adjusting the formula and process. The present invention does not contain harmful metal elements such as lead, is environmentally friendly, and can be used in food processing machinery.
[0029] 7. The present invention provides a MAX phase ceramic reinforced high temperature resistant composite friction material, the composite friction material has a hardness of 195-210 HV, a compressive strength of 883-1029 MPa, and a bending strength of 732-859 MPa. At the same time, the material has a low wear rate, a low and stable friction coefficient, and exhibits good comprehensive performance.
[0030] 8. The present invention has low cost, high economic benefit and wide application range, and is suitable for use under low, medium and high temperature working conditions. It can also be used for friction parts under harsh working conditions such as sliding bearings, bushings and sliders, and has a relatively broad application prospect. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 The flowchart of the preparation method of the composite friction material in the embodiment of the present invention is shown in FIG. DETAILED DESCRIPTION
[0032] The present invention will be further described in detail below in conjunction with specific embodiments.
[0033] A MAX phase ceramic reinforced high temperature resistant composite friction material, with the total mass of the material being 100%, the components and their mass percentages are: 76.0% to 94.0% copper alloy matrix, 3.0% to 12.0% composite reinforcement phase, and 3.0% to 12.0% lubrication phase; wherein the composite reinforcement phase is composed of Ti3SiC2, TiC and TiB2, the mass fraction of the composite reinforcement phase Ti3SiC2 is 60.0% to 80.0%, the mass fraction of TiC is 10.0% to 20.0%, and the mass fraction of TiB2 is 10.0% to 20.0%; the composite lubrication phase is composed of K2MoO4 and MoS2, the mass fraction of K2MoO4 is 40.0% to 60.0%, and the mass fraction of MoS2 is 40.0% to 60.0%; the material is obtained by ball milling and hot pressing sintering of the copper alloy matrix, the composite reinforcement phase and the composite lubrication phase.
[0034] Taking the total mass of the material as 100%, the components and their mass percentages are: Cu 58.0%-77.0%, Al 6.0%-9.5%, Ni 4.0%-6.5%, Fe 2.5%-4.0%, Mn 0.3%-1.0%, Co0.3%-1.0%, La2O3 0.3%-1.0%, composite strengthening phase 3.0%-12.0%, and lubricating phase 3.0%-12.0%.
[0035] The mesh size of the composite reinforcement phase is 200 to 300 meshes.
[0036] The mesh size of the composite lubricating phase is 200 to 300 meshes.
[0037] like Figure 1 As shown, a method for preparing a high temperature resistant composite friction material reinforced by MAX phase ceramics according to the present invention comprises the following steps:
[0038] (1) Ti3SiC2, TiC and TiB2 powders are mixed and wet-milled under inert gas protection, with a ball-to-material ratio of 4:1 to 6:1, a rotation speed of 250 to 350 r / min, and a ball milling time of 8 to 12 h to obtain a mixed powder; the mixed powder is placed in a sintering furnace for sintering, and the vacuum degree is less than or equal to 1×10 -1Pa, sintering temperature is 1200-1400℃, holding time is 5-10min, after sintering, the furnace is cooled, and the obtained block is ground under inert gas protection to obtain composite strengthening phase powder;
[0039] (2) mixing the copper alloy matrix, the composite strengthening phase powder and the composite lubricating phase powder, and ball milling them under inert gas protection, with a ball-to-material ratio of 1:1 to 2:1, a rotation speed of 100 to 150 r / min, and a ball milling time of 10 to 12 h to obtain a mixed powder;
[0040] (3) The mixed powder is placed in a sintering furnace for sintering, and the vacuum degree is less than or equal to 1×10 -1 Pa, the sintering temperature is 850-900℃, the sintering pressure is 35-40MPa, the holding time is 5-10min, and the furnace is cooled after sintering to obtain a MAX phase ceramic reinforced high temperature resistant composite friction material.
[0041] Preferably, in step (1), the heating rate is 100-150° C. / min.
[0042] Preferably, in step (1), during grinding, the grinding jar and the grinding balls are both made of tungsten carbide, the ball-to-material ratio is 1:1-2:1, the rotation speed is 100-150 r / min, and the grinding time is 6-8 h.
[0043] Preferably, in step (1), during grinding, the grinding is stopped every 10 minutes, and then continued after stopping for 2 minutes.
[0044] Preferably, in step (2), during ball milling, both the grinding jar and the grinding balls are made of tungsten carbide cemented carbide.
[0045] Preferably, in step (2), during ball milling, the mill is stopped every 5 minutes and then continued to run after stopping for 2 minutes.
[0046] Preferably, in step (3), during sintering, the heating rate is 100 to 150° C. / min.
[0047] Example 1
[0048] (1) Weigh 60.0 g of Ti3SiC2, 20.0 g of TiC, and 20.0 g of TiB2. Ti3SiC2, TiC, and TiB2 are all 200 mesh. Ball mill them under argon atmosphere. Add 2 ml of ethanol before ball milling. The ball-to-material ratio is 4:1. The speed is 250 r / min and the ball milling time is 8 h. The obtained mixed powder is placed in a sintering furnace for sintering. The vacuum degree is less than or equal to 1×10 -1Pa, heating rate of 100℃ / min, sintering temperature of 1200℃, holding time of 5min, cooling with the furnace after sintering, crushing the cooled loose block, and grinding in a ball mill under the protection of inert gas, ball-to-material ratio of 1:1, rotation speed of 100r / min, ball milling time of 6h, to obtain a composite strengthening phase powder of not less than 200 mesh.
[0049] (2) Weigh 77.0 g of Cu, 6.0 g of Al, 4.0 g of Ni, 4.0 g of Fe, 1.0 g of Mn, 1.0 g of Co, 1.0 g of La2O3, 3.0 g of composite strengthening phase powder (Ti3SiC2+TiC+TiB2), and 3.0 g of composite lubricating phase powder (1.5 g of K2MoO4, 1.5 g of MoS2), and mix them by mechanical ball milling. The grinding jar and grinding balls are both tungsten carbide cemented carbide, the ball-to-material ratio is 1:1, the rotation speed is 100 r / min, the ball milling time is 10 h, and the milling is stopped every 5 min. After stopping for 2 min, the milling is continued. After the ball milling is completed, a mixed powder is obtained.
[0050] (3) placing the mixed powder in a spark plasma sintering furnace for hot pressing sintering with a vacuum degree of less than 1×10 - 1 Pa, heating rate 100℃ / min, sintering temperature 850℃, applied pressure 35MPa, holding time 5min, cooling to room temperature with the furnace, to obtain a MAX phase ceramic reinforced high temperature resistant composite friction material.
[0051] The hardness of the material was tested with a Vickers hardness tester and was found to be 210HV. The mechanical properties were tested with a CMT-5205 universal material testing machine, with a compression and three-point bending displacement rate of 0.1mm / min. The material had a compressive strength of 1029MPa and a flexural strength of 859MPa.
[0052] The high temperature tribological properties were evaluated using a HT-1000 high temperature friction and wear tester. The dual ball was a 316 stainless steel ball, the load was 10N, the sliding speed was 0.15m / s, the friction radius was 5mm, the running time was 30min, and the test temperature was 25℃ and 550℃. The average friction coefficient of the material at room temperature was 0.29, and the average wear rate was 2.0×10 -4 mm 3 / N·m; the average friction coefficient at 550℃ is 0.51, and the average wear rate is 4.8×10 -4 mm 3 / N·m, and has good anti-friction and anti-wear performance. It can be seen that the material has a low and stable friction coefficient and wear rate, and has good anti-friction and anti-wear performance.
[0053] Example 2
[0054] (1) Weigh 75.0 g of Ti3SiC2, 13.0 g of TiC, and 12.0 g of TiB2. Ti3SiC2, TiC, and TiB2 are all 200 mesh. Ball mill them in an argon atmosphere. Add 2 ml of ethanol before ball milling. The ball-to-material ratio is 5:1. The speed is 300 r / min and the ball milling time is 10 h. Stop once every 10 min. After stopping for 2 min, continue to run. After the ball milling is completed, a composite strengthening phase powder is obtained. The obtained mixed powder is placed in a sintering furnace for sintering. The vacuum degree is less than or equal to 1×10 -1 Pa, heating rate is 120℃ / min, sintering temperature is 1300℃, holding time is 8min, cooling with the furnace after sintering, crushing the cooled loose block, and grinding in a ball mill under the protection of inert gas, ball-to-material ratio is 2:1, rotation speed is 120r / min, ball milling time is 7h, and a composite strengthening phase powder of not less than 200 mesh is obtained.
[0055] (2) Weigh 65.8 g of Cu, 9.5 g of Al, 6.5 g of Ni, 2.0 g of Fe, 0.3 g of Mn, 0.3 g of Co, 0.3 g of La2O3, 7.5 g of composite strengthening phase powder (Ti3SiC2+TiC+TiB2), and 7.5 g of composite lubricating phase powder (3.0 g of K2MoO4, 4.5 g of MoS2), and mix them by mechanical ball milling. The grinding jar and grinding balls are both tungsten carbide cemented carbide, the ball-to-material ratio is 1.5:1, the rotation speed is 125 r / min, the ball milling time is 11 h, and the mill is stopped every 5 min. After stopping for 2 min, it continues to run. After the ball milling is completed, a mixed powder is obtained.
[0056] (3) placing the mixed powder in a spark plasma sintering furnace for hot pressing sintering with a vacuum degree of less than 1×10 - 1 Pa, heating rate 130℃ / min, sintering temperature 880℃, applied pressure 37MPa, holding time 7min, cooling to room temperature with the furnace, to obtain a MAX phase ceramic reinforced high temperature resistant composite friction material.
[0057] The material was tested for performance using the same testing method as in Example 1. The material had a hardness of 205 HV, a compressive strength of 958 MPa, and a flexural strength of 789 MPa. The material had an average friction coefficient of 0.26 at room temperature, and an average wear rate of 1.7×10 -4 mm 3 / N·m; the average friction coefficient at 550℃ is 0.45, and the average wear rate is 4.2×10 -4 mm 3 / N·m, and has good anti-friction and anti-wear performance. It can be seen that the material has a low and stable friction coefficient and wear rate, and has good anti-friction and anti-wear performance.
[0058] Example 3
[0059] (1) Weigh 80.0g of Ti3SiC2, 10.0g of TiC, and 10.0g of TiB2. Ti3SiC2, TiC, and TiB2 are all 200 mesh. Ball mill them in an argon atmosphere. Add 2ml of ethanol before ball milling. The ball-to-material ratio is 6:1. The speed is 350r / min and the ball milling time is 12h. Stop once every 10min and continue to run after stopping for 2min. After the ball milling is completed, a composite strengthening phase powder is obtained. The obtained mixed powder is placed in a sintering furnace for sintering. The vacuum degree is less than or equal to 1×10 -1 Pa, heating rate is 150℃ / min, sintering temperature is 1400℃, holding time is 10min, cooling with the furnace after sintering, crushing the cooled loose block, and grinding in a ball mill under the protection of inert gas, ball-to-material ratio is 2:1, rotation speed is 150r / min, ball milling time is 8h, and a composite strengthening phase powder of not less than 200 mesh is obtained.
[0060] (2) Weigh 58.0 g of Cu, 8.0 g of Al, 6.5 g of Ni, 3.0 g of Fe, 1.0 g of Mn, 0.7 g of Co, 0.8 g of La2O3, 12.0 g of composite strengthening phase powder (Ti3SiC2+TiC+TiB2), and 12.0 g of composite lubricating phase powder (7.2 g of K2MoO4, 4.8 g of MoS2), and mix them by mechanical ball milling with a ball-to-material ratio of 2:1, a rotation speed of 150 r / min, and a ball milling time of 12 h. Stop once every 5 min, stop for 2 min, and continue running. After the ball milling is completed, a mixed powder is obtained.
[0061] (3) placing the mixed powder in a spark plasma sintering furnace for hot pressing sintering with a vacuum degree of less than 1×10 - 1 Pa, heating rate 150 ℃ / min, sintering temperature 900 ℃, applied pressure 40MPa, holding time 10min, cooling to room temperature with the furnace, to obtain a MAX phase ceramic reinforced high temperature resistant composite friction material.
[0062] The material was tested for performance using the same testing method as in Example 1. The material had a hardness of 195 HV, a compressive strength of 883 MPa, and a flexural strength of 732 MPa. The material had an average friction coefficient of 0.20 at room temperature, and an average wear rate of 1.3×10 -4 mm 3 / N·m; the average friction coefficient at 550℃ is 0.36, and the average wear rate is 3.8×10 -4 mm 3 / N·m, and has good anti-friction and anti-wear performance. It can be seen that the material has a low and stable friction coefficient and wear rate, and has good anti-friction and anti-wear performance.
[0063] Comparative Example 1
[0064] Compared with Example 3, the composite strengthening phase (Ti3SiC2+TiC+TiB2) is replaced by (TiC+TiB2) in Comparative Example 1, and the mass is the same as 12.0g. Other material components, contents, and preparation processes are consistent with those in Example 3. The material properties obtained in Comparative Example 1 are compared with those in Example 3 (Table 1). The results show that the compressive strength and flexural strength of Comparative Example 1 decrease, and the wear rate increases. This is because when the composite strengthening phase lacks the intermetallic compound Ti3SiC2, the bonding force between the strengthening phase and the matrix interface decreases, which in turn causes the strength and wear resistance to decrease.
[0065] Table 1 Comparison of Comparative Example 1 with Example 3
[0066]
[0067] Comparative Example 2
[0068] Relative to Example 3, the composite strengthening phase (Ti3SiC2+TiC+TiB2) is replaced by Ti3SiC2 in Comparative Example 2, and the mass is the same as 12.0g. Other material components, contents, and preparation processes are consistent with those in Example 3. Comparing the material properties obtained in Comparative Example 2 with those in Example 3 (Table 2), the results show that the compressive strength and flexural strength of Comparative Example 2 decrease, and the wear rate increases. This is because when TiC and TiB2 are missing, the strengthening effect of TiC and TiB2 on Ti3SiC2 and the copper alloy matrix cannot be produced, which results in a decrease in hardness, strength, and wear resistance.
[0069] Table 2 Comparison of Comparative Example 2 with Example 3
[0070]
[0071] Comparative Example 3
[0072] Compared with Example 2, Comparative Example 3 replaces the composite lubricating phase (K2MoO4+MoS2) with K2MoO4, and the mass is the same as 7.5g. The other material components, contents, and preparation processes are consistent with those of Example 2. The material properties obtained in Comparative Example 3 are compared with those in Example 2 (Table 3). The results show that the friction coefficient of Comparative Example 3 increases at room temperature. This is because the lubrication performance of MoS2 is better than that of K2MoO4 at room temperature, so the room temperature friction coefficient increases when the material does not contain MoS2.
[0073] Table 3 Comparison of Comparative Example 3 with Example 2
[0074]
[0075] Comparative Example 4
[0076] Compared with Example 2, Comparative Example 4 replaces the composite lubricating phase (K2MoO4+MoS2) with MoS2, and the mass is the same as 7.5g. The other material components, contents, and preparation processes are consistent with those of Example 2. The material properties obtained in Comparative Example 3 are compared with those in Example 2 (Table 3). The results show that the friction coefficient of Comparative Example 3 increases at 500°C. This is because the lubrication performance of K2MoO4 is better than that of MoS2 at high temperatures, so the high-temperature friction coefficient increases when the material does not contain K2MoO4.
[0077] Table 4 Comparison of Comparative Example 4 with Example 2
[0078]
[0079] Comparative Example 5
[0080] Compared with Example 3, the composite strengthening phase and composite lubricating phase contained in Comparative Example 5 exceed the specified range, and the copper alloy matrix content is lower than the specified range. The specific composition ratio is 54.0g of Cu, 8.0g of Al, 6.5g of Ni, 3.0g of Fe, 1.0g of Mn, 0.7g of Co, 0.8g of La2O3, 14.0g of composite strengthening phase powder (Ti3SiC2+TiC+TiB2), and 14.0g of composite lubricating phase powder (7.0g of K2MoO4, 7.0g of MoS2). Other preparation processes and process parameters are consistent with those of Example 3. The material properties obtained in Comparative Example 5 are compared with those in Example 3 (Table 5). The results show that the hardness, compressive strength, flexural strength, and friction coefficient of Comparative Example 5 decrease, and the wear rate increases. This is because when the amount of composite strengthening phase and composite lubricating phase added is too much, although the friction coefficient can be reduced, there are too many impurities and defects at the grain boundaries of the material, and the internal phase interface bonding force decreases, resulting in a decrease in strength.
[0081] Table 5 Comparison of Comparative Example 5 with Example 3
[0082]
[0083] Comparative Example 6
[0084] Compared with Example 1, Co and La2O3 are not added in Comparative Example 6, and the specific composition ratio of the materials is: 79.0g of Cu, 6.0g of Al, 4.0g of Ni, 4.0g of Fe, 1.0g of Mn, 3.0g of composite strengthening phase powder (Ti3SiC2+TiC+TiB2), and 3.0g of composite lubricating phase powder (1.5g of K2MoO4, 1.5g of MoS2). Other preparation processes and process parameters are consistent with those of Example 1. The material properties obtained in Comparative Example 6 are compared with those in Example 1 (Table 6). The results show that the hardness, compressive strength, and flexural strength of Comparative Example 6 decrease, and the wear rate increases. This is because when Co and La2O3 are missing, the refinement and dispersion strengthening effects cannot be produced, the hardness and strength of the material decrease, resulting in reduced wear resistance.
[0085] Table 6 Comparison of Comparative Example 6 with Example 1
[0086]
[0087] Comparative Example 7
[0088] Relative to Example 3, when preparing the composite strengthening phase (Ti3SiC2+TiC+TiB2) powder, Comparative Example 7 did not perform high-energy ball milling and high-temperature sintering, but only mixed by low-energy ball milling. The ball milling process is as follows: dry ball milling under argon protective atmosphere, ball-to-material ratio 1:1, rotation speed of 100r / min, stop once every 15min, stop 2min and continue ball milling, ball milling time is 8h. Other material components, contents, and preparation processes are consistent with those of Example 3. The material properties obtained in Comparative Example 7 are compared with those in Example 3 (Table 7), and the results show that the strength and wear resistance of the material obtained in Comparative Example 7 are reduced. This is because Comparative Example 7 did not perform high-energy ball milling and high-temperature sintering, resulting in TiC and TiB2 being unable to strengthen Ti3SiC2, and the dispersion and surface chemical energy of Ti3SiC2, TiC, and TiB2 are low, and the bonding force with the copper alloy matrix is reduced, so the material strength and wear resistance are reduced.
[0089] Table 7 Comparative Example 7 compared with Example 3
[0090]
[0091] Comparative Example 8
[0092] Relative to Example 1, when hot pressing and sintering are used to prepare the composite material in Comparative Example 8, the sintering temperature is higher than the specified range and the sintering pressure is lower than the specified range. The specific sintering process is as follows: the sintering temperature is 920°C, the pressure is 30MPa, the constant temperature and pressure are maintained for 5 minutes, the hot pressing sintering is terminated, and the furnace is cooled to room temperature. The other material components, contents, and preparation processes are the same as those in Example 1. The material properties obtained in Comparative Example 8 are compared with those in Example 1 (Table 8). The results show that the hardness and strength of the material obtained in Comparative Example 8 decrease, and the wear rate increases. This is because the sintering temperature of Comparative Example 8 is too high, resulting in changes in the phase composition of the copper alloy matrix, and segregation of the finished product occurs, and the α phase and κ phase formed by Cu and Al are uneven. At the same time, the sintering pressure of Comparative Example 8 is too low, resulting in a decrease in the density, hardness and strength of the material.
[0093] Table 8 Comparative Example 8 compared with Example 1
[0094]
[0095] In summary, the invention includes but is not limited to the above embodiments. Any equivalent substitution or partial improvement made under the spirit and principle of the invention shall be deemed to be within the protection scope of the invention.
Claims
1. A MAX phase ceramic reinforced high temperature resistant composite friction material, characterized in that: Taking the total mass of the material as 100%, the components and their mass percentages are: copper alloy matrix 76.0% to 94.0%, composite strengthening phase 3.0% to 12.0%, composite lubricating phase 3.0% to 12.0%; wherein the composite strengthening phase is composed of Ti3SiC2, TiC and TiB2, the mass fraction of the composite strengthening phase Ti3SiC2 is 60.0% to 80.0%, the mass fraction of TiC is 10.0% to 20.0%, and the mass fraction of TiB2 is 10.0% to 20.0%; the composite lubricating phase is composed of K2MoO4 and MoS2, the mass fraction of K2MoO4 is 40.0% to 60.0%, and the mass fraction of MoS2 is 40.0% to 60.0%; the material is obtained by ball milling and hot pressing sintering of the copper alloy matrix, the composite strengthening phase and the composite lubricating phase; Taking the total mass of the material as 100%, the components and their mass percentages are: Cu 58.0% to 77.0%, Al 6.0% to 9.5%, Ni 4.0% to 6.5%, Fe 2.5% to 4.0%, Mn 0.3% to 1.0%, Co 0.3% to 1.0%, La2O3 0.3% to 1.0%, composite strengthening phase 3.0% to 12.0%, composite lubricating phase 3.0% to 12.0%; The preparation method of the material comprises the following steps: (1) Ti3SiC2, TiC and TiB2 powders are mixed and wet-milled under inert gas protection, with a ball-to-material ratio of 4:1 to 6:1, a rotation speed of 250 to 350 r / min, and a ball milling time of 8 to 12 h to obtain a mixed powder; the mixed powder is placed in a sintering furnace for sintering, and the vacuum degree is less than or equal to 1×10 -1 Pa, sintering temperature is 1200-1400℃, holding time is 5-10min, after sintering, the furnace is cooled, and the obtained block is ground under inert gas protection to obtain composite strengthening phase powder; (2) mixing the copper alloy matrix, the composite strengthening phase powder and the composite lubricating phase powder, and ball milling them under inert gas protection, with a ball-to-material ratio of 1:1 to 2:1, a rotation speed of 100 to 150 r / min, and a ball milling time of 10 to 12 h to obtain a mixed powder; (3) The mixed powder is placed in a sintering furnace for sintering, and the vacuum degree is less than or equal to 1×10 -1 Pa, the sintering temperature is 850-900℃, the sintering pressure is 35-40MPa, the holding time is 5-10min, and the furnace is cooled after sintering to obtain a MAX phase ceramic reinforced high temperature resistant composite friction material.
2. The MAX phase ceramic reinforced high temperature resistant composite friction material according to claim 1, characterized in that: The mesh size of the composite reinforcement phase is 200 to 300 meshes.
3. The MAX phase ceramic reinforced high temperature resistant composite friction material according to claim 1, characterized in that: The mesh size of the composite lubricating phase is 200 to 300 meshes.
4. The MAX phase ceramic reinforced high temperature resistant composite friction material according to claim 1, characterized in that: In step (1), the heating rate is 100-150°C / min.
5. The MAX phase ceramic reinforced high temperature resistant composite friction material according to claim 1, characterized in that: In step (1), during grinding, the grinding jar and the grinding balls are both made of tungsten carbide, the ball-to-material ratio is 1:1-2:1, the rotation speed is 100-150 r / min, the grinding time is 6-8 h, and the grinding is stopped every 10 min, and then continued to run after stopping for 2 min.
6. The MAX phase ceramic reinforced high temperature resistant composite friction material according to claim 1, characterized in that: In step (2), during ball milling, the grinding pot and the grinding balls are both made of tungsten carbide hard alloy.
7. The MAX phase ceramic-reinforced high temperature resistant composite friction material according to claim 1, characterized in that: In step (2), during ball milling, the mill was stopped every 5 minutes and continued to run after stopping for 2 minutes.
8. The MAX phase ceramic reinforced high temperature resistant composite friction material according to claim 1, characterized in that: In step (3), during sintering, the heating rate is 100-150°C / min.
Citation Information
Patent Citations
Self-lubricating copper-Ti3SiC2-NbSe2 composite material and preparation method thereof
CN102703161A
Brake block friction material taking Mn+1XAn lamellar compound as antifriction phase and preparation method
CN103184385A
Powder metallurgy friction material for high-speed train braking and preparation method of powder metallurgy friction material
CN109518100A
A friction material, a brake pad including the friction material, and a method for preparing the brake pad.
CN110284083B
Copper-based powder metallurgy friction materials and their preparation methods
CN112011748B